The effect of the country’s efficiency on economic growth in the Arab countries, with special reference to the case of Algeria. Standard analytical study for the period (1996-2014) - Becherair, Omrane; Tahtane, Mourad (Dirassat Journal Economic Issue, 2016)
This paper aims to examine the impact of institutional efficiency on economic growth in Arab countries using panel data model over the period (1996 -2014), the results indicate that; the control of corruption index has no significant effect on economic growth in Algeria. However, the results show a negative effect on the rate of economic growth in the sample. The research found that the improvement in the level of participation and accountability, and the level of effectiveness of the government lead to improve the rate of GDP growth. the results show also that, the level of political stability and absence of violence, and the effectiveness of government affect the rate of growth in Algeria.